2009
DOI: 10.1016/s1130-1473(09)70183-6
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar epidural abscess caused by brucella species: report of two cases

Abstract: SummarySpinal epidural abscess due to Brucella species is usually associated with spondylodiscitis. Urgent surgical decompression should be performed in cases with moderate to severe neurological deficits particularly if progressive. We report clinical features of two cases operated for lumbar epidural abscess caused by Brucella species. Early surgical decompression combined with medical treatment could decrease progression of neurological findings or the severity of complications. Iatrogenic dural tear at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Positive blood culture is crucial as a definitive diagnostic tool. Furthermore, the culture of surgical or biopsy specimens may reveal a localized infection caused by Brucella species, such as neurobrucellosis [3, 12]. …”
Section: Discussionmentioning
confidence: 99%
“…Positive blood culture is crucial as a definitive diagnostic tool. Furthermore, the culture of surgical or biopsy specimens may reveal a localized infection caused by Brucella species, such as neurobrucellosis [3, 12]. …”
Section: Discussionmentioning
confidence: 99%
“…In case of Brucella-related epidural abscess, the source is most probably adjacent vertebrae. Several cases of brucellosis related epidural abscess have been reported in the literature [6,[12][13][14]. A study by İzci et al in 2005 reported that a patient who had presented with leg and sciatic pain was found to have spinal epidural abscess on MRI examination and development of Brucella melitensis in the blood culture [13].…”
Section: Discussionmentioning
confidence: 99%
“…Infrequently, spinal abscess may be the cause of sciatica and may demonstrate similar symptoms, thus being easily mistaken for another form of pathology [5]. Initial diagnosis may include spinal degenerative conditions, musculoskeletal injuries, malignancy and infectious agents, most often discitis or vertebral osteomyelitis as well as some of the rarer medical emergencies [2,3,5].…”
Section: Introductionmentioning
confidence: 99%
“…Tomaz Velnar, Gorazd Bunc the most common region of involvement, spinal intradural abscess may be formed anywhere along the spinal cord, most commonly involving the thoracic region [3,10,12]. Thus, a high level of suspicion must be present when managing a patient with back pain in order to avoid confusion with more common spinal problems, for example a herniated disc [2].…”
mentioning
confidence: 99%